2013
DOI: 10.1017/s0950268813002185
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years of active bat rabies surveillance in Germany: a detailed analysis and future perspectives

Abstract: SUMMARYIn Germany, active bat rabies surveillance was conducted between 1993 and 2012. A total of 4546 oropharyngeal swab samples from 18 bat species were screened for the presence of EBLV-1-, EBLV-2-and BBLV-specific RNA. Overall, 0·15% of oropharyngeal swab samples tested EBLV-1 positive, with the majority originating from Eptesicus serotinus. Interestingly, out of seven RT-PCR-positive oropharyngeal swabs subjected to virus isolation, viable virus was isolated from a single serotine bat (E. serotinus). Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 37 publications
(104 reference statements)
2
25
2
Order By: Relevance
“…While the detection of EBLV-1 antibodies is frequently reported in field bat studies, the mortality of numerous bats from one site is unusually reported. The detection of viral RNA and viable virus in oropharyngeal swabs that we reported in the study is in accordance with previous studies [16]. Repeated detection of viral RNA in saliva swabs from recaptured bats was not observed in this study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While the detection of EBLV-1 antibodies is frequently reported in field bat studies, the mortality of numerous bats from one site is unusually reported. The detection of viral RNA and viable virus in oropharyngeal swabs that we reported in the study is in accordance with previous studies [16]. Repeated detection of viral RNA in saliva swabs from recaptured bats was not observed in this study.…”
Section: Discussionsupporting
confidence: 93%
“…We showed here a high detection rate of neutralising EBLV-1 antibodies in the colony, with 49% of seroconverting bats. The detection of EBLV-1 virus-neutralizing antibodies is frequent in bats [16, 18], with a seroprevalence varying according to the site location, species and time. The high rate of seropositive bats in this study is probably indicative of an efficient virus transmission coupled to a rapid circulation of EBLV-1 in the colony.…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, six rabies cases in Daubenton’s bats have been typed as EBLV-2 [33,34,35,41], and five genome sequences were available to be included in this study. Notably, only one case was detected in the frame of routine rabies surveillance, whilst the other five isolates were only found during enhanced surveillance programmes targeting all dead found bats [34].…”
Section: Resultsmentioning
confidence: 99%
“…These conclusions may differ from that found by other authors in other countries where the lack of findings suggests the absence of an active rabies infection (Mani et al, 2017). Thereby, active bat surveillance for RABV in other countries has also reported a very low prevalence of viral antigen or nucleic acid in healthy bat populations (Picard-Meyer et al, 2011;Nokireki et al, 2013;Ellison et, 2014;Schatz et al, 2014) The lack of a sampling with longer duration and/ or with greater expansion of the search area could be a limiting factor of this study for the lack of positive results. Also as a limitation of the study, a larger number of specimens could have been sent for diagnosis, which would increase the chance of detection.…”
Section: Carollia Perspicillata D Rotundus and A Lituratusmentioning
confidence: 94%